2010
DOI: 10.1021/ie1010806
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Study on the Adsorption of CFC-115 and HFC-125 on Activated Carbon and Silicalite-1

Abstract: The adsorption isotherms of chloro-1,1,2,2,2-pentafluoroethane) and HFC-125 (1,1,1,2,2pentafluoroethane) on Vruf activated carbon (Calgon Carbon Corp.; brand code, VRU-F) and silicalite-1 have been accurately measured at pressures up to 120 kPa and temperatures ranging from 273 to 348 K. The To ´th or dual-site Langmuir (DSL) model appropriately describes the equilibrium data for the adsorptives CFC-115 and HFC-125 on Vruf carbon or silicalite-1, respectively. Because HFC-125 molecule has a higher packing eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…Adsorptive separations offer energy-efficient alternatives to distillation. Towards this end, Peng et al 76 have reported the pure component isotherm data for CFC-115 and HFC-125 in MFI zeolite; see Fig. 28a.…”
Section: Separation Of Chlorofluorocarbons With Mfi Zeolitementioning
confidence: 99%
“…Adsorptive separations offer energy-efficient alternatives to distillation. Towards this end, Peng et al 76 have reported the pure component isotherm data for CFC-115 and HFC-125 in MFI zeolite; see Fig. 28a.…”
Section: Separation Of Chlorofluorocarbons With Mfi Zeolitementioning
confidence: 99%
“…This work aims to study the capture by adsorption of the three most commonly employed pure F‐gases in domestic refrigeration (R‐32, R‐125, and R‐134a). The adsorption of these gases on activated carbons (ACs), zeolites, or metal–organic frameworks (MOFs) at various temperature and pressure ranges has been reported in the literature . Even though MOFs present in general higher adsorption capacities, ACs are the most commonly used adsorbents in many industrial processes due to their large micropore and mesopore volumes, high surface area, variety of surface functional groups, low cost, and wide range of available morphologies …”
Section: Introductionmentioning
confidence: 99%
“…The adsorption of R‐32, R‐125, R‐134a, and of commercial refrigerants containing these F‐gases on other ACs has been already studied in the literature. However, to the best of our knowledge, this work is the first publication reporting on a systematic study of the adsorption of those three pure F‐gases on four different ACs with different porous characteristics in order to select the best material for the separation of commercial refrigerants.…”
Section: Introductionmentioning
confidence: 99%
“…The isotherm data can be fairly described by the combined fitting (Peng et al 2010;Zhu et al 2001), i.e., Eqs. (1) and (2), as shown in Fig.…”
Section: Adsorption Propertiesmentioning
confidence: 99%